Strategies For Utilizing Augmented Reality Media By Islamic Religious Education Teachers To Enhance Students’ Learning Motivation In The Digital Era - Nur Jihan Nabilah Al Muhdhar; Rahmad Hakim (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
The rapid transformation of digital technology compels Islamic Religious Education (IRE) teachers to adopt learning approaches that are more innovative, interactive, and aligned with the needs of digital-native students. Augmented Reality (AR) has emerged as a promising instructional medium due to its capacity to create immersive learning experiences, visualize abstract Islamic concepts, and promote deeper engagement. This study examines strategies for utilizing AR by IRE teachers to enhance students’ learning motivation in the digital era. Using a literature review methodology, ten peer-reviewed studies published between 2016 and 2025 were analyzed based on their empirical relevance to AR integration, motivational outcomes, and pedagogical strategies. Results indicate that AR enhances student motivation by increasing attention, curiosity, autonomy, and participation—particularly regarding abstract, procedural, or spatially complex Islamic content such as prayer movements, Hajj rituals, Islamic historical sites, and tajwīd rules. Effective teacher strategies include needs-based planning, alignment with Cognitive Theory of Multimedia Learning (CTML) and Cognitive Load Theory (CLT), structured AR-supported practice, autonomy-supportive activities, and authentic assessments. The study concludes that AR is a powerful but design-dependent tool whose success relies heavily on teacher readiness, pedagogical alignment, and technological accessibility. Recommendations for practice and future research are provided to ensure scalable and sustainable AR integration in IRE classrooms.